TO DETERMINE AGRONOMIC AND ECONOMIC ADVANTAGES OF INTERCROPPING SUNFLOWER WITH COMMON BEANS - MICHAEL MASOMBO; Dr. Martin M. Koome; Dr. David Maushimiyimana; Prof Peter A.Kamau Kamau (IJRDO- Journal of Educational Research, 2020)
A field research trial on intercropping sunflower (Helianthusannuus) and common beans (Phaseolus vulgaries) was first held at the Kaimosi Agricultural Training Centre (ATC) farm in Nandi County in the short season of 2016. The purpose of the research was to investigate the agronomic and economic potential of intercropping the two crops. Particularly, the field trial was done in randomized complete block design (RCBD) coupled with three imitations. Sunflower variety H8998 and Mwitemania common beans (GLP 92) were sown simultaneously. The treatments included sole beans B (45 x 10 cm), sole sunflower S1 (75 x 30 cm), sole sunflower S2 (90 x 30 cm), and the intercrops of sunflower/bean (single and double rows of beans with the two sunflower spacing S1 and S2). Clearly, the results exhibited that sunflower plant height, head diameter, 100 seed weight, and number of pods per plant in case common bean was not significantly affected while days to maturity for beans and the yields of these two food crops were massively effected by the intercropping systems. Land equivalent ratio (LER) ranged between 1.32 and1.54 for all the four intercropping systems. Monetary equivalent ratio (MER) varied between 0.99 and 1.20 with three out of the four intercrops combinations having MER > 1.0. Sunflower S2 (90 x30 cm) intercropped with double rows of beans had highest LER (1.54) and MER (1.20). The results indicate there was land use advantage and economic efficiency where each LER and MER value exceeded 1.0. Therefore, the intercropping method needs to be intensively practiced to maximize total crop production per unit area.